The Making and Characterization of Banggai Tuber (Dioscorea Spp) Edible Film - Sitti Rahmawati, Alfiana Aulia, Siti Nuryanti, Suherman (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to make edible film and to determine the characterization of Banggai tuber (Dioscorea Spp) starch based edible film. The plasticizer types used were glycerol and sorbitol. The best treatment in this research was edible film with the usage of 80°C temperature and glycerol in the amount of 2%(b/v) and sorbitol 2 %(b/v) with the results obtained respectively were for thickness 0,478 mm and 0,488 mm, tensile strength 0,007 Kgf/mm2 and 0,021 Kgf/mm2, elongation percentage 27,76% and 12,36, pH 6,52 and 7,6, water absorption 46,62% and 14,37%, solubility 20,14,8% 14,8%, the speed of water vapor transmission 0,2209 gram/hour m2 and 0,4560 gram/hour m2, the result of FTIR test shows that the process of making edible film in this research is Physics mixture process, and the period of shelf life of edible film at room temperature is 6 days and at cold temperature is 8 days..